MINI REVIEW: SINTESIS NANOKOMPOSIT TiO2/Fe3O4 DAN PENGGUNAANNYA SEBAGAI FOTOKATALIS - Putriani, Elsa Avrilia; Hindryawati, Noor (PROSIDING SEMINAR KIMIA, 2025)
Mini Review on Synthesis and Characterization of TiO2/Fe3O4 Nanocomposites as Photocatalysts aims to compare the photocatalytic activity of TiO2/Fe3O4 nanocomposites in the process of dye degradation. TiO2/Fe3O4 nanocomposites are used because they have good photocatalytic activity properties in the process of dye photocatalysis. Based on existing literature, TiO2/Fe3O4 nanocomposites can be synthesized using several methods such as sol-gel, impregnation, precipitation and coprecipitation. Then applied to the degradation of dyes by considering time, type of light, dye concentration and catalyst. So, this article reviews the latest developments in TiO2/Fe3O4 nanocomposites, especially in photocatalysts of methylene blue and methyl orange dyes by looking at the concentration of TiO2/Fe3O4 used. Keywords : Photocatalysis, Fe3O4 Magnetite, Nanocomposites, TiO2.